Pelatihan Pembuatan Saus Cabai sebagai Upaya Diversifikasi Produk Olahan bagi Kelompok Tani Mandiri Sejahtera Desa Wowoli, Kecamatan Toari - Handayani, Fitrianti; Mu’arief, Nur Syamsi; R, Mustafa; Tojang, Djunarlin; Afa, Musadia; Adelina, Fitrah; Mpia, La; Muhsafaat, La Ode; Maretik, Maretik; Abid, Nur Azizah M. (Universitas Nusantara PGRI Kediri, 2026)
This community service program aims to empower the Mandiri Sejahtera Farmers Group in Wowoli Village, Toari District, Kolaka Regency, through training in chili sauce production. The main challenges faced by farmers are low chili prices during the main harvest and losses due to rapid chili perishability due to lack of post-harvest handling. The program was implemented in a participatory manner, based on the principle of learning by doing. This included outreach, preparation of ingredients and tools, training in chili sauce production (boiling, crushing, mixing spices, heating, and packaging), mentoring participants, and evaluation through discussions and questions and answers. The results of the program demonstrated improved skills and understanding of chili processing technology, the creation of a local product called